Valuation of the training received in university regarding the utility for work by Catalan graduates - S. Fachelli; D. Montolio (Multidisciplinary Journal for Education, Social and Technological Sciences)
This article examines the factors that influence graduate valuations of the education/training they received at university in terms of its utility or applicability in the workplace. Drawing on the 2014 survey conducted by the Agency for the Quality of the Catalan University System, among students that graduated in 2010, we test three hypotheses. The first states that graduate valuation of the training received at university in terms of its utility for the workplace is higher among those who are currently employed in high quality jobs; the second that this valuation is higher among graduates employed in higher occupational categories; and, the third, that higher valuations are given by individuals with better academic records. The methodology used to test the three hypotheses is based on both descriptive and econometric techniques that allow us to control for specific individual characteristics and specific characteristics of the degree subjects studied. Preliminary empirical results allow us to verify two of the three hypotheses. The main contribution of this paper is to provide some initial insights into a relationship not frequently examined in the literature and to offer some empirical evidence that counters the typical “matching” standpoint taken on the relationship between education/training and level of employment.